THE IMPACT OF PHYSICAL ACTIVITY AND NON-PHARMACOLOGICAL INTERVENTIONS ON NEUROPLASTICITY IN EPILEPSY: MECHANISMS, EVIDENCE, AND CLINICAL IMPLICATIONS - Jakub Przerwa (International Journal of Innovative Technologies in Social Science, 2025)
Epilepsy is a chronic brain disorder characterized by recurrent epileptic seizures and long-lasting alterations in neuronal excitability and connectivity. Although pharmacological and surgical interventions currently play a primary role in epilepsy treatment, growing evidence indicates that non-pharmacological approaches-such as brain stimulation, cognitive training, and physical exercise-can induce neuroplastic mechanisms underlying this group of disorders, which may have important clinical implications.The aim of this review is to summarize experimental and clinical evidence regarding the effects of non-pharmacological techniques on brain plasticity in epilepsy. Numerous animal studies suggest that physical activity-both aerobic and resistance training-may reduce seizure frequency, improve cognitive functions, and stimulate hippocampal neurogenesis. Physical exercise has also been shown to promote synaptic reorganization, modulate GABAergic and glutamatergic systems, improve mitochondrial function and cerebral perfusion, and increase the expression of neurotrophic factors such as BDNF and IGF-1. However, further research is needed to identify biomarkers of neuronal plasticity and optimize the effectiveness of these interventions. This review aims to highlight the importance of a multidirectional- including non-pharmacological-therapeutic strategy in epilepsy management.